The dynamic expression of SOX17 in germ cells from human female foetus and adult ovaries after specification - Luo, Ying-Yi; Jie, Hui-Ying; Huang, Ke-Jun; Cai, Bing; Zhou, Xiu; Liang, Ming-Yi; Zhou, Can-Quan; Mai, Qing-Yun (Frontiers in Endocrinology, 2023)
SOX17 has been identified as a critical factor in specification of human primordial germ cells, but whether SOX17 regulates development of germ cells after sex differentiation is poorly understood. We collected specimens of gonad ridge from an embryo (n=1), and ovaries from foetuses (n=23) and adults (n=3). Germ cells were marked with SOX17, VASA (classic germ cells marker), phosphohistone H3 (PHH3, mitosis marker) and synaptonemal complex protein 3 (SCP3, meiosis marker). SOX17 was detected in both cytoplasm and nucleus of oogonias, and oocytes of primordial follicles and primary follicles from 15 to 28 gestational weeks (GW). However, it was exclusively expressed in cytoplasm of oogonias at 7 GW, and in nucleus of oocytes in secondary follicles. Coexpression rates of SOX17 in VASA+ germ cells ranged from 81.29% to 97.81% in foetuses. Co-staining rates of SOX17 and PHH3 or SCP3 were 0%-34% and 0%-57%, respectively. Interestingly, we distinguished a subpopulation of SOX17+ VASA- germ cells in fetal ovaries. These cells clustered in the cortex and could be co-stained with the mitosis marker PHH3 but not the meiosis marker SCP3. In conclusion, the dynamic expression of SOX17 was detected in human female germ cells. We discovered one SOX17+ VASA- germ cells population clustering at the cortex of ovaries. While we couldn’t find the relationship between the mitosis or meiosis and SOX17, VASA staining in germ cells. Our findings provide insight into the potential role of SOX17 involving germ cells maturation after specification, although the mechanism is unclear and needs further investigation.